Clinical features and outcomes of spitzoid proliferations in children and adolescents. (1st August 2019) - Bartenstein, D.W.; Fisher, J.M.; Stamoulis, C.; Weldon, C.; Huang, J.T.; Gellis, S.E.; Liang, M.G.; Schmidt, B.; Hawryluk, E.B.
Summary: Background: Spitzoid proliferations range from Spitz naevi to melanomas. There are few studies describing clinical features and outcomes in the paediatric population. Objectives: To determine the clinical features and outcomes of a large paediatric cohort with histopathologically confirmed Spitz tumours. Methods: This was a retrospective cohort study of patients seen at Boston Children's Hospital who were aged < 20 years and had a histopathological diagnosis of spitzoid proliferation from 1 January 1994 to 23 October 2012. Results: In total 595 patients with 622 spitzoid proliferations were identified (median age 7·4 years, interquartile range 4·6–11·7). Overall 512 proliferations (82·3%) were typical, 107 (17·2.%) were atypical and three (0·5%) were melanomas. The median ages at biopsy were 7·4, 7·2 and 17·2 years, respectively, and there was a significant difference in age at biopsy for patients with typical or atypical proliferations vs. melanoma ( P < 0·01). Among samples with positive margins ( n = 153), 55% (54 of 98) of typical proliferations, 77% (41 of 53) of atypical proliferations and 100% (two of two) of melanomas were re‐excised. Six patients had sentinel lymph node biopsy performed, with three patients demonstrating nodes positive for melanocytic cells. Within a median follow‐up of 4·1 years for the full cohort there were no related deaths. Conclusions: Spitz tumours have strikingly benign outcomes in the paediatric population, although this study is limited by the low number of melanomas and restriction to a single paediatric institution. Aggressive management recommendations should be reconsidered for children and adolescents with banal‐appearing Spitz naevi, based on the clinically indolent behaviour in this cohort.